Dopamine Neurons That Cotransmit Glutamate, From Synapses to Circuits to Behavior - Eskenazi, Daniel; Malave, Lauren; Mingote, Susana; Yetnikoff, Leora; Ztaou, Samira; Velicu, Vlad; Rayport, Stephen; Chuhma, Nao (Frontiers in Neural Circuits, 2021)
Discovered just over 20 years ago, dopamine neurons have the ability to cotransmit both dopamine and glutamate. Yet, the functional roles of dopamine neuron glutamate cotransmission and their implications for therapeutic use are just emerging. This review article encompasses the current body of evidence investigating the functions of dopamine neurons of the ventral midbrain that cotransmit glutamate. Since its discovery in dopamine neuron cultures, further work in vivo confirmed dopamine neuron glutamate cotransmission across species. From there, growing interest has led to research related to neural functioning including roles in synaptic signaling, development, and behavior. Functional connectome mapping reveals robust connections in multiple forebrain regions to various cell types, most notably to cholinergic interneurons in both the medial shell of the nucleus accumbens and the lateral dorsal striatum. Glutamate markers in dopamine neurons reach peak levels during embryonic development and increase in response to various toxins, suggesting dopamine neuron glutamate cotransmission may serve neuroprotective roles. Findings from behavioral analyses reveal prominent roles for dopamine neuron glutamate cotransmission in responses to psychostimulants, in positive valence and cognitive systems and for subtle roles in negative valence systems. Insight into dopamine neuron glutamate cotransmission informs the pathophysiology of neuropsychiatric disorders such as addiction, schizophrenia and Parkinson Disease, with therapeutic implications.